2021
DOI: 10.1504/mejm.2021.111988
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence and conflict management: an execution of organisational learning, psychological empowerment and innovative work behaviour in Chinese higher education

Abstract: Dynamic environmental challenges to create and improve value continuously urge the higher education institutions (HEI) to come up with and maintaining higher standards. This study investigated organizational learning, psychological empowerment and innovative work behaviour as mediators between emotional intelligence (EI) and conflict management. Data were collected from twelve educational institutes from Xi'an and Sichuan China. The survey was addressed to faculty members ranging from lecturers to professors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 66 publications
(113 reference statements)
0
35
0
Order By: Relevance
“…HEIs, in the modern world, create value through available knowledge and skills in order to remain competitive. HEIs are nowadays, eager to hire personnel who possess a fair degree of EI to cope with the pressure to develop the mechanisms for learning outcomes [ 3 ], who in turn enable the students to counter every situation with EI and to emerge as an efficient learner out of any given pressure situation [ 5 ]. The investigation relating to EI and SLOs in HEIs showed that students with greater ability to handle emotions and pressure situations are more likely to enhance their learning outcomes.…”
Section: Discussion Conclusion and Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…HEIs, in the modern world, create value through available knowledge and skills in order to remain competitive. HEIs are nowadays, eager to hire personnel who possess a fair degree of EI to cope with the pressure to develop the mechanisms for learning outcomes [ 3 ], who in turn enable the students to counter every situation with EI and to emerge as an efficient learner out of any given pressure situation [ 5 ]. The investigation relating to EI and SLOs in HEIs showed that students with greater ability to handle emotions and pressure situations are more likely to enhance their learning outcomes.…”
Section: Discussion Conclusion and Practical Implicationsmentioning
confidence: 99%
“…However, East Asia and especially China has challenged the predominance of the education system of the ‘West’ [ 1 , 2 ]. Research and higher education activities in China are at beginning stage [ 3 ] The nature of the activities on the part of Chinese students, the growth of professionalism in higher education institutions (HEIs), educational inequalities and rural-urban and gender disparities are vital factors underlying the infancy of research in China [ 4 ]. Zhoc, Chung [ 5 ], explained that Hong Kong HEIs have lengthened their three-year education system to four years within a discipline favouring early specialisation in a quest to enhance student learning outcomes (SLOs).…”
Section: Introductionmentioning
confidence: 99%
“…It is worthwhile to note that the combined sample of HEI academic and administrative personnel was undertaken on the suggestion of Zhoc, Chung [3], who recommended that studies should include diverse operational tiers of HEIs to ensure the generalizability of EI and learning outcomes. Furthermore, academicians and administrative individuals are investigated in Chinese HEIs on more than one occasion [6,7]. A survey was used for data collection and distributed to a large population, improving its reliability and generalizability [5].…”
Section: Population Sample and Data Collection Proceduresmentioning
confidence: 99%
“…First, there are limited strategies for adopting EI in Chinese higher education [7]. In addition, Fall, Kelly [8] highlighted the need to explain the importance of EI in the educational sector.…”
Section: Introductionmentioning
confidence: 99%
“…In the two-dimensional relationship between superiors and superiors, employees who perceive trust will get more emotional input, support and dependence from superiors. This will increase the employees' intrinsic motivation to work and enable them to obtain higher psychological acceptance, which in turn affects their work behavior and performance [28,29] . Therefore, the research model of this article aims to explore the relationship between employees' perceived trust, psychological empowerment and work performance in the context of organizational management.…”
Section: Theoretical Modelmentioning
confidence: 99%